Sarcocystis cristata sp. nov. (Apicomplexa, Sarcocystidae) in the imported great blue turaco Corythaeola cristata (Aves, Musophagidae) - Máca, Ondřej; González-Solís, David (Parasites & vectors, 2021)
BACKGROUND: Species of Sarcocystis are parasitic protozoa in poikilothermic and homeothermic animals. Out of the 26 valid species in birds as intermediate hosts, none has been reported in those of the order Musophagiformes, such as the great blue turaco Corythaeola cristata (Vieillot, 1816), which is a bird endemic to Central and Western Africa. The examination of great blue turacos imported from the Central Africa Republic to Czech Republic allowed the morphological and molecular characterization of a new species of Sarcocystis. METHODS: Four turacos imported from the Central Africa Republic to a private breeder (Czech Republic) underwent parasitological examination for the presence of sarcocysts through wet mounts of breast, heart and leg muscles. Found parasites were molecularly and histologically studied by four loci (18S rRNA, 28S rRNA, ITS1 and cox1) and haematoxylin and eosin staining, respectively. RESULTS: Three out of four examined birds harboured numerous sarcocysts in the breast and leg muscles. No macroscopic lesions where observed. Sarcocysts were microscopic, elongate and ribbon-shaped with a wall characterised by the presence of finger-shaped villar protrusions and filled with numerous elongate, banana-shaped bradyzoites, 11.87-14.84 × 2.05-2.92 µm in size. The new species was most closely related to Sarcocystis albifronsi, Sarcocystis anasi, Sarcocystis atraii, Sarcocystis chloropusae, Sarcocystis rileyi, Sarcocystis wenzeli and Sarcocystis sp. isolate from chicken in the four loci. CONCLUSIONS: To our knowledge, this is the first species of Sarcocystis found in a musophagiform bird worldwide. Genetically, S. cristata sp. nov. represents a distinct species. Phylogenetic analyses are useful for predicting potential definitive hosts of the new Sarcocystis species.
Keywords: západní Afrika; RNA ribozomální 18S; Phylogeny; Africa, Western; Birds; sarkocystóza; zvířata; genetická variace; Czech Republic; ptáci; Sarcocystosis; protozoální DNA; Česká republika; RNA, Ribosomal, 28S; Sarcocystis; RNA ribozomální 28S; Genetic Variation; Animals; DNA, Protozoan; fylogeneze; RNA, Ribosomal, 18S